Genetic Diversity, Habitat Relevance and Conservation Strategies of the Silver Carp in the Yangtze River by Simple Sequence Repeat - Luo, Yu-Ting; Fang, Di-An; Zhou, Yan-Feng; Xu, Dong-Po; Peng, Yun-Xin; Zhang, Min-Ying; Mao, Cheng-Cheng; Tang, Xue-Mei; Xu, Jun; You, Yang (Frontiers in Ecology and Evolution, 2022)
The spatial distribution of fish individuals is affected by habitat conditions and species ecological characteristics, and it also reflects the longtime adaptation to habitat at the phenotypic and genotypic level. Adaptation to a typical habitat over a long period of time causes fish species to form a distinct geographic population. As a typical river-lake migratory fish, the silver carp habitat selection was determined by its migration preference and genetic features. In this study, 15 microsatellite fluorescent markers combined with capillary electrophoresis were used to analyze the genetic diversity, genetic differentiation, and structure of wild silver carp populations in the Sanzhou (SZ), Hukou (HK), Anqing (AQ), Zhenjiang (ZJ), and Rugao (RG) sections of the Yangtze River. The results showed that 15 simple sequence repeat (SSR) loci exhibited medium to high polymorphisms (polymorphic information content (PIC) range 0.466-0.918. The overall genetic diversity in the Yangtze River was high, with the average value of Shannon’s information index ranging from 1.559 to 1.668. The numbers of alleles (Ne) ranged from 1.630 to 10.100. The mean of the expected heterozygosity (He, 0.690–0.721) was higher than the mean of the observed heterozygosity (Ho, 0.598–0.646), and the genetic variation mainly originated from within the population (94.69%). However, some populations face the risk of inbreeding (F>1). Interestingly, there was a single genetic structure for the population in the HK section, which indicated that population differentiation may have occurred to the silver carp in this river section, and they may also possess aggregation characteristics specific to the river-lake-connected (RLC) habitat. The results mostly support the hypothesis that the RLC habitat is essential for geographic population formation. The potential impact of special habitats on natural populations should be considered, and continuous surveys on population dynamics should be performed.